Metabolism of Flavonoids in Novel Banana Germplasm during Fruit Development - Dong, Chen; Hu, Huigang; Hu, Yulin; Xie, Jianghui (Frontiers in Plant Science, 2016)
Banana is a commercially important fruit, but its flavonoid composition and characteristics has not been well studied in detail. In the present study, the metabolism of flavonoids was investigated in banana pulp during the entire developmental period of fruit. ‘Xiangfen 1,’ a novel flavonoid-rich banana germplasm, was studied with ‘Brazil’ serving as a control. In both varieties, flavonoids were found to exist mainly in free soluble form and quercetin was the predominant flavonoid. The most abundant free soluble flavonoid was cyanidin-3-O-glucoside chloride, and quercetin was the major conjugated soluble and bound flavonoid. Higher content of soluble flavonoids was associated with stronger antioxidant activity compared with the bound flavonoids. Strong correlation was observed between antioxidant activity and cyanidin-3-O-glucoside chloride content, suggesting that cyanidin-3-O-glucoside chloride is one of the major antioxidants in banana. In addition, compared with ‘Brazil,’ ‘Xiangfen 1’ fruit exhibited higher antioxidant activity and had more total flavonoids. These results indicate that soluble flavonoids play a key role in the antioxidant activity of banana, and ‘Xiangfen 1’ banana can be a rich source of natural antioxidants in human diets.